2007
DOI: 10.1002/jbm.b.30835
|View full text |Cite
|
Sign up to set email alerts
|

Dose effects of cross‐linking polyethylene for total knee arthroplasty on wear performance and mechanical properties

Abstract: Wear performance and mechanical properties of cross-linking polyethylene (XLPE) tibial inserts were investigated using a knee simulator, scanning electron microscopy (SEM), and a small punch test (SPT). Ultrahigh molecular weight PE made from GUR1050 resin was irradiated at doses ranging from 0 to 200 kGy and then machined into tibial inserts followed by annealing. The knee simulator was run for up to four million cycles. As the radiation dose increased from 0 to 100 kGy, the wear rate decreased dramatically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 29 publications
4
32
1
Order By: Relevance
“…Wear testing of pristine CoCr femoral components against virgin and highly crosslinked UHMWPE tibial inserts reflected documented trends in the literature [14] in that the mean wear rate decreased significantly (p < 0.001) with each increase in the radiation dose examined in this study (Figure 4). The mean wear rates (± standard deviations) of the virgin, 5-XLPE, and 7.5-XLPE tibial inserts were 23.4 ± 2.4 mm 3 /Mc, 10.9 ± 0.9 mm 3 /Mc, and 6.4 ± 0.6 mm 3 /Mc, respectively.…”
Section: Wear Resistancesupporting
confidence: 78%
See 1 more Smart Citation
“…Wear testing of pristine CoCr femoral components against virgin and highly crosslinked UHMWPE tibial inserts reflected documented trends in the literature [14] in that the mean wear rate decreased significantly (p < 0.001) with each increase in the radiation dose examined in this study (Figure 4). The mean wear rates (± standard deviations) of the virgin, 5-XLPE, and 7.5-XLPE tibial inserts were 23.4 ± 2.4 mm 3 /Mc, 10.9 ± 0.9 mm 3 /Mc, and 6.4 ± 0.6 mm 3 /Mc, respectively.…”
Section: Wear Resistancesupporting
confidence: 78%
“…It is well understood that the degree of crosslinking appropriate for a particular application is a delicate balance between improvements in wear and reduced mechanical properties resulting from increased crosslinking [14]. With that in mind, the crosslinked UHMWPE formulations currently marketed for TKA typically utilize lower crosslink densities than those marketed for THA.…”
Section: Introductionmentioning
confidence: 99%
“…As there are no studies at present directly comparing the wear performance of these two bearing materials, it is difficult to comment upon the relative effect of the material on the wear rates observed within this study. However, several studies have demonstrated a significant reduction with increased cross-linkage for polyethylene tibial inserts [40][41][42]. Both bearings had cobalt-chrome femoral and tibial components, and therefore it may be expected that the contribution of the relative composition of the bearing on the overall wear may be less compared with the effect of bearing design or insert material.…”
Section: Discussionmentioning
confidence: 99%
“…Work by Asano et al [6] used the small punch test metrics to investigate the optimum irradiation dose suitable for crosslinking of knee bearings. Work by Asano et al [6] used the small punch test metrics to investigate the optimum irradiation dose suitable for crosslinking of knee bearings.…”
Section: Overview and Metrics Of The Small Punch Testmentioning
confidence: 99%